Aneurysm of Vieussens' arterial ring in a patient studied with coronary computed tomography. (January 2015) - De Cecco, Carlo N.; Rengo, Marco; Muscogiuri, Giuseppe; Caruso, Damiano; Bellini, Davide; Laghi, Andrea
Abstract : We present the case of Vieussens' arterial ring aneurysm in a patient who underwent coronary computed tomography. Vieussens' arterial ring is a remnant of the embryonic conotruncal circle. Only four cases of aneurysm are described in literature. This is the first reported case in which a dilated Vieussens' arterial ring is observed without coronary stenosis.